2013
DOI: 10.1128/genomea.00005-13
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the “Indian Bison Type” Biotype of Mycobacterium avium subsp. paratuberculosis Strain S5

Abstract: We report the 4.79-Mb genome sequence of the “Indian Bison Type” biotype of Mycobacterium avium subsp. paratuberculosis strain S5, isolated from a terminally sick Jamunapari goat at the CIRG (Central Institute for Research on Goats) farm in India. This draft genome will help in studying novelties of this biotype, which is widely distributed in animals and human beings in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
(10 reference statements)
1
13
0
Order By: Relevance
“…through irrigation) and seafood. Further research is required to examine how hardy M. paratuberculosis is in its spore-like state and how long it survives in manure storage and composting to better understand the risk of contaminating other potential environmental sources of M. paratuberculosis for humans (Lamont et al, 2012 (Singh et al, 2013;Ahlstrom et al, 2015). The multitude of molecular methods used to date has been a barrier to meaningful synthesis of molecular epidemiological results (Ahlstrom, et al, 2015;Muellner, et al, 2015), therefore as data from whole genome sequencing become more widely used in epidemiological investigations, researchers should seek consensus on target markers to aid in the comparability of results across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…through irrigation) and seafood. Further research is required to examine how hardy M. paratuberculosis is in its spore-like state and how long it survives in manure storage and composting to better understand the risk of contaminating other potential environmental sources of M. paratuberculosis for humans (Lamont et al, 2012 (Singh et al, 2013;Ahlstrom et al, 2015). The multitude of molecular methods used to date has been a barrier to meaningful synthesis of molecular epidemiological results (Ahlstrom, et al, 2015;Muellner, et al, 2015), therefore as data from whole genome sequencing become more widely used in epidemiological investigations, researchers should seek consensus on target markers to aid in the comparability of results across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Citations retrieved from all databases were imported into reference management software RefWorks (Copyright 2015, ProQuest LLC) and de-duplicated. Search verification included screening reference lists of seven review articles (Anon, 2010;Grant, 2010;Kaevska and Hruska, 2010;Mor-Mur and Yuste, 2010;Singh et al, 2010a;Over et al, 2011;Carta et al, 2013) and five systematic reviews published on M. paratuberculosis (Feller et al, 2007;Abubakar et al, 2008;Eltholth et al, 2009;Okura et al, 2012;Fernandez-Silva et al, 2014).…”
Section: Search Strategymentioning
confidence: 99%
“…Mycobacterium avium subspecies paratuberculosis (MAP), cause the incurable Paratuberculosis or Johne"s disease, it is an infectious disease of the intestinal tract, primarily infects domestic livestock (Singh et al, 2011;Singh et al, 2014a). It is globally known that milk and milk products made from pasteurized milk of endemically infected domestic livestock contain live MAP bacilli.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of JD is both expensive and impractical (Harris and Barletta, 2001), therefore, vaccination is the only promising way in controlling JD. Development of indigenous vaccine for commercial exploitation is underway and in earlier studies on 'indigenous vaccine' (Singh et al, 2007a;Singh et al, 2013c;Singh et al, 2013d) though showed good response when used in herds/flocks of goats, sheep, cattle and buffaloes, however, the dose rate of 2.5 and 5.0 mg per animal in small and large ruminants, respectively for lifetime were accrued from the International literature (Perez et al, 1995). During trials of vaccine in cattle with poor nutrition status, cows exhibited increase in shedding of MAP at around 8 months post vaccination after showing decrease in shedding up to 8 months after vaccination (personal observations).…”
Section: Introductionmentioning
confidence: 99%